Indonesian Language Literacy Strategies for BIPA Learners in Thailand: A Narrative Literature Review - Al Illahiyah, Lailatul Husna; Aninditya Sri Nugraheni; Oky Akmal Rustandi; Johan Alamsah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2026)
This study aims to analyze effective strategies for teaching Indonesian literacy to Thai learners in the Indonesian as a Foreign Language (BIPA) context. The study is motivated by the rapid development of BIPA in Thailand, alongside persistent challenges in students’ reading and writing skills caused by linguistic differences, cultural distance, and limited pedagogical adaptation. The main argument of this study is that Indonesian literacy learning for Thai students requires an integrated approach that combines linguistic competence, communicative practice, and intercultural understanding. This study employed a literature review method within the framework of Second Language Acquisition theory. Relevant studies on BIPA learning, Indonesian literacy, and second language pedagogy were analyzed thematically to identify dominant instructional approaches, their contributions, and the factors influencing their implementation in the Thai educational context. The findings show that genre-based, task-based, and intercultural approaches are the three main strategies used in BIPA literacy learning in Thailand. The genre-based approach supports students’ understanding of text structure and authentic language use. The task-based approach strengthens communicative competence through meaningful learning activities. Meanwhile, the intercultural approach helps learners understand Indonesian language use within its social and cultural contexts. The success of these approaches is influenced by students’ proficiency levels, linguistic differences between Thai and Indonesian, learning culture, availability of bilingual and authentic materials, and teachers’ pedagogical competence. This study implies that BIPA literacy instruction in Thailand should be designed through an integrated literacy strategy combining genre-based, task-based, and intercultural approaches. However, as a literature-based study, the findings are limited to conceptual and secondary data analysis. Further empirical research is needed to test the effectiveness of the proposed strategy in classroom practice.